KCPR Archives, 1985 - 1987 (1985)
KCPR Archives 1985 - 1986 [00:00] Rick Lopes - ASI outings - Record cut off [00:07] K. Speir - Cal Poly Sports Car Club [00:35] Jon Jaeger - Soul Patrol Promo [01:37] Jim Barnhardt - Cal Poly Ski Club [02:24] John Carrol - Atascadero Rec. Dept. [03:03] Dean Clark - Komedy Klub Promo [03:37] Duane Mieliwocki - Dreams are Real, but [04:40] Scott Larsen - Signatures [05:44] John Carrol - Dance Concert [06:29] Duane Mieliwocki - ASI outings [07:19] Kaly / Kramer - Sunday Request Party [08:08] Joseph Mama Productions I.D [08:34] Paisley Productions I.D. [09:02] Killer B - New Releases / Album Review Promo [09:52] Joseph Mama Productions - The Spirit / James Harmond Band [10:56] Scott Larsen - The Spirit / Bolshoi [12:10] Dawn Rangel - Alarm ASI concerts promo [13:20] Al Savay - The Jazz Show [14:08] Jennifer Biorkland - M.S (U.G.L.Y. Bartenders) [15:13] Jungle Jim Barnhardt - Consumer Product Safety Commision [16:20] Duane Mieliwocki - Burnt Dog I.D. [16:35] Scott Larsen - Alarm / Long Ryders [17:42] Scott Larsen - Mojo Nixon in Studio B KCPR Archives 1986 - 1987 [18:20] Frank Warren Intro of KCPR Archives 1986 - 1987 [18:35] Scott Larsen - Cure Promo [19:43] Scott Larsen - Find out about KCPR promo [20:55] John Carrol - Belly Dancing [21:35] Ric Turner - Microwave Dog I.D. [21:53] Doug Kramer - Gremlin I.D. [22:06] Greg Kopchinski - Rock of Ages [23:11] Frank Warren - Oldies Promo [23:44] Scott Larsen - Peter Case at the Spirit [24:51] Bruce Gordon - Stress Reduction Center [25:42] Scott Carter & Dave Riveness - Happy Time trivia show [26:14] Timothy Chase - 120 Min Tech Dream [27:17] Bruce Gordon - Glass Show [28:19] Frank Warren - Alternate Groove [29:27] Jon Jaeger - What does it all mean I.D. [29:49] Jennifer Biorkland - Travel center [30:21] Frank Warren, Jon Jaeger, Bruce - Lone Justice Promo [31:25] Toi Phillips - Butthole Surfers Promo [32:50] Scott McGowen - Alarm ASI Concerts [33:53] Lee Benson - The Wizard of Oz [34:50] Wendy Manrer & Jon Jaeger - Soundtracks [36:00] Scott Carter & Dave Riveness - Happy Time trivia show [36:33] Scott Larsen - Jonathan Richman Promo [38:09] Scott Larsen - Dead Milkmen [39:15] Jon Jaeger - Game Theory [40:24] Jaeger & Lenzer - Replacements [41:36] Frank Warren - Soul Patrol - Summer [43:17] Frank Warren - Wire Train Special [44:23] Frank Warren & Anna Lekola - KCPR Auction Soap and Auction Promo [46:57] Frank Warren & Dave Potovsky - KCPR Canned Food Drive